2013
DOI: 10.5173/ceju.2013.03.art14
|View full text |Cite
|
Sign up to set email alerts
|

Original Paper Double J stent reduces the efficacy of extracorporeal shock wave lithotripsy in the treatment of lumbar ureteral stones

Abstract: IntroductionWe evaluated the effect of the presence of a double J stent on the efficacy of extracorporeal shock wave lithotripsy (ESWL) in the treatment of lumbar ureteral stones.Material and methodsBetween January 2007 and February 2012, we performed a retrospective cohort study. Forty–four patients were treated by ESWL for lumbar ureteral stones and included into two groups for the analysis: group 1, non–stented (n = 27) and group 2, stented patients (n = 17). Treatment efficacy was evaluated by abdominal X–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In patients with an MSL>10 mm, the success rate was significantly lower in the stenting group, but in those with an MSL≤10 mm, there was no difference in success rate between the 2 groups. These findings are similar to those of Pettenati et al [12], in which SWL success was lower in the stenting group only with larger stones, defined as a size >8 mm. The differential effects of MSL may be explained to some degree by the theories mentioned above.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In patients with an MSL>10 mm, the success rate was significantly lower in the stenting group, but in those with an MSL≤10 mm, there was no difference in success rate between the 2 groups. These findings are similar to those of Pettenati et al [12], in which SWL success was lower in the stenting group only with larger stones, defined as a size >8 mm. The differential effects of MSL may be explained to some degree by the theories mentioned above.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, recent studies found that ureteral stents negatively affect SWL success or SFR. For example, Pettenati et al [12] demonstrated that the presence of a ureteral stent negatively affects the efficacy of SWL in treating lumbar ureteral stones These authors found that the success rate with stenting was significant lower than the rate without stenting in patients with stones larger than 8 mm. Ozkan et al [13] also reported that SFR was significantly higher in their stentless group than in their stenting group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 In fact, having a stent may impede the passage of fragments following SWL. A trial consisting of patients with ureteral stones between 4 to 10 mm undergoing SWL were randomized to a stent or no stent.…”
Section: Stentingmentioning
confidence: 99%
“…Similar to the issue of ureteral stenting and SWL complications, the effects of SWL on stone-free rates (SFRs) are also controversial [7910]. Several recent studies have demonstrated that ureteral stenting reduces the SFR following SWL [111213], but the significance of this finding is debated. Thus, the current study was conducted to evaluate the effects of ureteral stenting and stone characteristics on ureteral stone clearance and to estimate the probability of one-session success in SWL patients with ureteral calculi according to whether they underwent ureteral stenting or exhibited various other factors.…”
Section: Introductionmentioning
confidence: 99%